Guía de técnicas de estudio para mejorar el rendimiento académico, de los estudiantes de octavo año de educación básica paralelo b de la unidad educativa Marieta de Veintimilla, período 2017-2018. - Collaguazo Lopez, Celenia Maribel (2018)
The Research called STUDY TECHNIQUES GUIDE TO IMPROVE THE ACADEMY PERFORMANCE, OF THE STUDENTS OF EIGHTH-GRADE CLASS B OF THE MARIETA OF VEINTIMILLA HIGH SCHOOL PERIOD 2017-2018, has the general objective of the implement a Study Techniques Guide to improve the academy performance of the eight-grade class B students. Was a descriptive, cross sectional and pre-experimental study; the methods used were: scientific, deductive, inductive, analytical, synthetic, historical-logical and statistic. The qualifications of the second partial were used as (prediagnostic) and the qualifications of the third partial as (post-diagnostic) based in the grading scale of the Ecuador’s Ministry of Education in a sample of 35 students. Results (prediagnostic) were: Next students Reach the Learnings Required with notes of 4,01-6,99 94,2% in Natural Sciences; 91,4% in School Projects; 74,3% in Cultural Education-Artistic; and 62,9% in Mathematics; likewise they Did not reach the Learnings Required with qualifications ?4, 40,0% in Social Studies and 28,6% in Tongue and Literature. Afterwards of the application of the proposal (post-diagnostic) the pupils Reach the Learnings Required (notes of 7,00-8,99) 82,9% in Natural Sciences; 80% in Mathematics; 74,3% in Social Studies; 71,4% in Tongue and Literature, while they Dominate the Learnings Required (qualifications of 9,00-10,00) 17,1% in School Projects and 11,4% in Cultural EducationArtistic. In conclusion the students improved his academy performance in the subjects of the eighth-grade, validating like this the proposal of intervention; therefore it is important that the teachers give continuity to the use of the techniques of study to follow optimizing the students' school performance.